Analisis ketepatan dan kesesuaian kandungan ilmu sintaksis dalam buku teks KBSM / Nik Muhammad Rozi Nik Yusoff - Nik Muhammad Rozi , Nik Yusoff (2018)
This study discusses the accuracy and suitability of the contents of the syntax found in Arabic textbooks Integrated Secondary School Curriculum (ICSS), which are used by students form one to form five in Malaysia. In this study researcher used qualitative methods to take content analysis design to examine and analyze the content of the syntax found in textbooks. Sampling using data syntax found in five books on the Arabic text. The analysis was based on two themes namely factual accuracy include concepts, definitions, explanations and examples. The second theme is the suitability of content, as measured by the criteria of frequency. The results showed that the contents of the syntax found in Arabic textbooks covers all the basic header syntax comprehensive Arab but not exhaustive. Offences involving syntactic fact is small, including language errors. The study also found almost all the topics discussed meet the criteria predetermined frequency. However, the distribution and composition of the title should be reviewed to make it more consistent with those criteria. In conclusion, the contents of the syntax found in textbooks are suitable but there is still room for improvement in terms of coverage, distribution and composition of the title. This study basically pioneered the study area for further study in selecting the suitable headings in accordance with the priorities and needs in order to apply an increased level of Arabic language proficiency among the people in general and students in particular.